SOCIAL DEVELOPMENT AND EDUCATION OF THE YOUTH IN THE HOLY QURAN - - (Fırat University, 2021)
Civilized nature of human being is gaining competence in building civilization when developed nicely in a family environment. Therefore, it is necessary to build the family on a solid foundation and the members should be aware of the rights and duties. The Holy Quran revals this fact by establishing the bases of the family upon solid foundations and announcing widely the rights and obligations of members with theoretical and practical examples. In particular, positive behaviour models placed in the parables are conferred of important information about how to soialize the generations. The socialization principle which is taken by the Holy Quran for the family which is the narrowest element of the community and for the community as a whole, brings the awarenes of fraternity based on the unity of faith and that the rights should be kept above all else. Thus, rights-based strong family plot will expand to create a solid community and, ultimately, the whole humanity will establish the peaceful world which is a basic requirement of the caliphate. Quran suggests for the parents and adults of the community that the starting point is to accommodate the generations, from the family to near and far surroundings, to establish social bonds around the awarenes of the rights and belief in monotheism. It informs that financial and body worships, especially the ones performed in congregation, have an important role in constructing social milieu and to maure the members through fusing them together. All of these Qur'anic quotations are not just in the form of bringing suggestions to the new generations but offering social role models with moral values. Quran has demonstrated, with examples from every section of life, that if adults transfers good morals in to the life through good examples, this will pave the way for the young people to create a good social environment.